THE WINDOW INFORMATION FOR INVESTOR ON ACCOUNTING PROFIT FORECASTING - Ratna Wijayanti Daniar Paramita (JURNAL TERAPAN MANAJEMEN DAN BISNIS, 2017)
This study aimed to obtain empirical evidence, examine and explain he factors (leverage, persistence, growth, size and beta) that affect informativeness of earnings and its application in the financial statements at Manufacturing Companies listed in the Indonesia Stock Exchange 2013-2016. Research on the relationship between stock returns within come to determine the extent of their relationship are many who use earnings figures as the dependent variable regressed with stock returns as the independent variables are calculated by different methods. This method measures the magnitude of abnormal stock returns in response to the expected components of a company's reported earnings by using Earning Response Coefficient (ERC). Plan for data analysis in this study will be conducted using Path Analysis with analysis application of Moment Structure (AMOS).Conclusions of this study is significant influence of Leverage, Persistence profit and growth to Informativeness of earnings, either directly or through intervening variables Size and Beta.